Cross-Situational Consistency of Affective Experiences across Cultures - OISHI, Shigehiro (Institutional Knowledge at Singapore Management University, 2004)
This study examined cross-situational consistency of affective experiences using an experience-sampling method in Japan, India, and the United States. Participants recorded their moods and situations when signaled at random moments for 7 days. The authors examined relative (interindividual) consistency and absolute (within-person) consistency. They found stable interindividual differences of affective experiences across various situations (mean r = .52 for positive affect .51 for negative affect) and cultural invariance of the cross-situational consistency of affective experiences. Simultaneously, the authors found a considerable degree of within-person cross-situational variation in affective experiences, and cultural differences in within-person cross-situational consistency. Thus, global affective traits exist among non-Western samples, but the degree to which situations exert an influence on the absolute level of affective experience varies across cultures.